Who are the civilians in the wars of South Sudan?. (October 2019) - Kindersley, Nicki; Rolandsen, Øystein H
This longitudinal study explores the place of the civilian populations in the wars of what is now South Sudan. Using a broad range of empirical evidence, we trace the evolution of conflict practices and norms from the 1800s to today. Two main insights stand out: First, since the initial colonial incursions, local residents have been strategic assets to be managed and exploited, and thus populations are not just legitimate targets in conflicts but also key resources to capture and control. Second, violent governance structures and practices have been created and reformed through these generations of coercive rule and civil wars. These two issues have undermined, and redefined, the distinction between military and civilian actors. This analysis does not excuse the massive and systematic violence against the general population of these countries. However, without due consideration of these deeply engraved historical systems and logics of violent governance, today's brutal conflicts become incomprehensible, and there is a significant risk that international approaches to mitigating this violence – such as Protection of Civilians camps – become incorporated into these systems rather than challenging them.